2019
DOI: 10.1002/mus.26428
|View full text |Cite
|
Sign up to set email alerts
|

Use of collision tests to identify physiological differences between the median and ulnar nerves

Abstract: Introduction: Median and ulnar nerves are used in comparative electrophysiological studies. We analyzed the conduction values in these hand nerves in healthy volunteers to find any physiological differences between them. Methods: We performed standard conduction studies and conduction velocity distribution (CVD) tests with estimation of 3 quartiles in 31 healthy right‐handed volunteers (17 women, 14 men) with a mean age of 44.8 ± 15.5 years. Results: The conduction velocities in all quartiles of CVD tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…As a result, safer and more effective surgical interventions, and individually selected, appropriate rehabilitation treatments could be easier to determine. Although our research needs to be extended, e.g., by application of CHEPS, we can state, based on the present study, and our previous findings on motor conduction in the median and ulnar nerves (Koszewicz et al, 2019), that physiological differences between these two nerves should be fully included during the examination of hand…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As a result, safer and more effective surgical interventions, and individually selected, appropriate rehabilitation treatments could be easier to determine. Although our research needs to be extended, e.g., by application of CHEPS, we can state, based on the present study, and our previous findings on motor conduction in the median and ulnar nerves (Koszewicz et al, 2019), that physiological differences between these two nerves should be fully included during the examination of hand…”
Section: Discussionmentioning
confidence: 77%
“…This is important, because these nerves are often compared in the evaluation of hand nerve pathology, above all in carpal tunnel syndrome examination ( Sable, 1998 ; Sander et al, 1999 ; Nouraei et al, 2015 ; Barton et al, 2016 ; Wyner and Dissabandara, 2018 ). In our previous study ( Koszewicz et al, 2019 ) we showed faster motor conduction velocities in the ulnar nerve using a more advanced neurophysiological technique: the conduction velocity distribution (CVD) test. The findings confirmed the presence of more larger fibers in the ulnar than in the median nerve.…”
Section: Introductionmentioning
confidence: 95%
“…The peripheral nerves consist of axons of different diameter, unmyelinated and myelinated with different thicknesses of the myelin sheaths. The conduction velocity depends on both the diameter of the axons and the thickness of the myelin (Ugrenović et al, 2016;Koszewicz et al, 2019). The collision method of CVD allowed us to explore virtually the whole spectrum of fibers forming the group A nerve fibers connecting alpha motoneurons and extrafusal muscle fibers including large and small myelinated fibers (Kiziltan et al, 2007;Ni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We performed CVD tests based on the antidromic recurrent block of the proximal stimulus (the so-called collision method) (Dalkilic et al, 2015;Koszewicz et al, 2019;Ni et al, 2020) in the median, ulnar, peroneal nerves. Two supramaximal stimuli were delivered subsequently at the distal and proximal stimulation points along the nerves, the two evoked CMAPs were recorded.…”
Section: Cvd Studymentioning
confidence: 99%
See 1 more Smart Citation